2018
DOI: 10.1002/ece3.4362
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diagnosis of a rare myrmecochorous species, Plagiorhegma dubium (Berberidaceae): Historical genetic bottlenecks and strong spatial structures among populations

Abstract: Distribution of genetic variation over time and space is relevant to demographic histories and tightly linked to ecological disturbances as well as evolutionary potential of an organism. Therefore, understanding the pattern of genetic diversity is a primary step in conservation and management projects for rare and threatened plant species. We used eight microsatellite markers to examine the level of genetic diversity, spatial structure, and demographic history of Plagiorhegma dubium, a rare myrmecochorous herb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 79 publications
(133 reference statements)
0
3
0
Order By: Relevance
“…would likely further exacerbate their critical conservation status given the stereotypical impression of Berberis as agricultural weeds. Additionally, because both P. dubium ( Lee et al, 2018 ) and S. hexandrum ( Liu W. et al, 2016 ) are also rare and exploited for traditional medicines, recognizing and elevating these two distinct species to the generic rank also confers an effective conservation strategy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…would likely further exacerbate their critical conservation status given the stereotypical impression of Berberis as agricultural weeds. Additionally, because both P. dubium ( Lee et al, 2018 ) and S. hexandrum ( Liu W. et al, 2016 ) are also rare and exploited for traditional medicines, recognizing and elevating these two distinct species to the generic rank also confers an effective conservation strategy.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, because both P. dubium (Lee et al, 2018) and S. hexandrum (Liu W. et al, 2016) are also rare and exploited for traditional medicines, recognizing and elevating these two distinct species to the generic rank also confers an effective conservation strategy.…”
Section: Infrafamilial Classification Of Berberidaceaementioning
confidence: 99%
“…Accordingly, the role of population genetic diversity has become increasingly significant in terms of responding to biodiversity loss and subsequent conservation strategies ( des Roches et al, 2021 ; Hohenlohe et al, 2021 ; Stange et al, 2021 ). For example, Lee et al (2018) suggested risk in deleting a rare myrmecochorous herb, Plagiorhegma dubium from the Red List of South Korea based on the pattern of population genetic diversity of simple sequence repeat data despite the recent growth of census population sizes.…”
Section: Introductionmentioning
confidence: 99%